1987
DOI: 10.4141/cjss87-004
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Methods for Determining the Evapotranspiration and Drainage Components of the Soil Water Balance

Abstract: Two simple techniques for separating soil moisture loss into drainage and evapotranspiration for cropped conditions were compared. The study was conducted during May through September 1983 at Ellerslie, Alberta. One technique, the field capacity method, utilized soil tension at − 4 kPa to demarcate the cessation of drainage; the other technique, the gradient method, utilized changes in soil moisture status relative to fallow conditions, to mark the onset of moisture extraction by roots. Both methods estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Selected characteristics for both soil series are presented in Table I. Additional site and soil characteristics have been published for the Malmo (Pawluk, 1986;Maule and Chanasyk, 1987) and for the Breton (McGill et al, 1987;Fyles et al, 1988) soils. Average frost-free days at Ellerslie and Breton are 109 and 80, respectively.…”
Section: Comparison Of Cropping Systemsmentioning
confidence: 99%
“…Selected characteristics for both soil series are presented in Table I. Additional site and soil characteristics have been published for the Malmo (Pawluk, 1986;Maule and Chanasyk, 1987) and for the Breton (McGill et al, 1987;Fyles et al, 1988) soils. Average frost-free days at Ellerslie and Breton are 109 and 80, respectively.…”
Section: Comparison Of Cropping Systemsmentioning
confidence: 99%
“…Unsaturated water fluxes below the root zone have been determined for the semi-arid region of the Canadian prairies for undulating landscapes in the Brown soil zone (de Jong and Zentner 1985), hummocky landscapes in the Dark Brown zone (Woods et al 2006;Si and de Jong 2007), as well as hummocky (Zebarth and de Jong 1989) and rolling (Maule and Chanasyk 1987) landscapes in the Black soil zone. However, we are unaware of any research that has quantified vertical unsaturated flux below the root zone for mid and lower slope positions within inclined, low-relief, and longerslope landscapes of the Dark Brown soil zone.…”
mentioning
confidence: 99%
“…Goss et al (1984) O'sullivan (1995) observed that in a humid environment on land cropped to spring bjrrley most changes in soil water occurred in the top 0.4 m. The rate of soil drying was greater when the land was plowed prior to seeding than when seeding was by direct drilling; however, the greater water uptake from topsoil by spring barley grown on the plowed treatment, did not increase yields. In a subhumid environment, Maul6 and Chanasyk (1987) (Fig. a).…”
mentioning
confidence: 99%